1990
DOI: 10.4049/jimmunol.145.1.36
|View full text |Cite
|
Sign up to set email alerts
|

Human T cell receptor-gamma delta-expressing T-cell lines recognize MHC-controlled elements on autologous EBV-LCL that are not HLA-A, -B, -C, -DR, -DQ, or -DP.

Abstract: HLA-loss variants of an EBV-transformed B lymphoblastoid cell line (EBV-LCL) 721 were used to investigate whether human MHC molecules other than known class I or class II were involved in autologous T cell responses. Bulk lymphocyte cultures of purified T cells primed to an autologous variant EBV-LCL that fails to express HLA-class II and has reduced cell surface HLA-class I expression, and oligoclonal TCR-gamma delta-bearing lines derived from them, could lyse both this EBV-LCL and an independently derived, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The putative activating ligand was of cellular origin rather than a viral structure, and was upregulated on activated B cells. LCL-responsive clones did not show predominant CDR3 sequences, and no evidence of oligoclonal expansion was found [138][139][140][141]. Remarkably, Vδ1 cells are also amplified in patients with acute B lymphocytic leukaemias [142,143], and in one study these cells were reported to lyse EBV neg B-CLL cells.…”
Section: γδ and Ebv/hhv-4mentioning
confidence: 99%
“…The putative activating ligand was of cellular origin rather than a viral structure, and was upregulated on activated B cells. LCL-responsive clones did not show predominant CDR3 sequences, and no evidence of oligoclonal expansion was found [138][139][140][141]. Remarkably, Vδ1 cells are also amplified in patients with acute B lymphocytic leukaemias [142,143], and in one study these cells were reported to lyse EBV neg B-CLL cells.…”
Section: γδ and Ebv/hhv-4mentioning
confidence: 99%